Combined effect of sodium hypochlorite and ultraviolet-C on Pseudomonas Aeruginosa biofilms on stainless steel used in food processing - Aningat, Jan Carlo C.; Gabriel, Alonzo A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
The purpose of this research was to determine the effects of hypochlorite alone or in combination with UV-C as sanitizing agent against Pseudomonas aeruginosa on a 316 stainless steel type with a mirror finish. The effect of acid stress on the hypochlorite susceptibility of P. aeruginosa was also studied. Survival curves generated from both acid-stress and non-stress hypochlorite inactivation revealed a biphasic inactivation behavior characterized by an initial faster log linear inactivation followed by a slower inactivation tail. Results from stress study showed that P.aeruginosa is able to resist acid stress following hypochlorite treatment. Calculated hypochlorite D-values ranged from 3.88 (50 ppm) to 10.68 s (200 ppm). The maximum log reductions prior to the inactivation tail of hypochlorite treated P. aeruginosa on 316 MR steel ranged from 0.48 log CFU/cm2 (50 ppm ) to 0.74 log CFU/cm2 (200 ppm). The sequential hypochlorite and UV-C inactivation study produced logarithmic linear death curves, and the D-values determined ranged from 11.72 s (100 ppm) to 134.10 s (200 ppm). The maximum log reductions of the combination treatment of P. aeruginosa on 316 MR steel ranged from 0.86 log CFU/cm2 (50 ppm ) to 0.89 log CFU/cm2 (100 ppm). These results showed that the sequential treatment of hypochlorite and UV-C may be used to achieve better inactivation of P.aeruginosa biofilms.
Thesis Classification: P
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Hypochlorites